Impact of lower-volume training on physical fitness adaptations in team sports players: A systematic review and meta-analysis - Clemente, F. M.; Ramirez-Campillo, R.; Moran, J.; Zmijewski, P.; Silva, R. M.; Randers, M. B. (Sports Medicine - Open, 2025)
Background A small number of reviews have explored lower- versus higher-volume training in non-athletes, but the growing challenge of congested schedules in team sports highlights the need to synthesize evidence specific to team sport athletes. Thus, the objectives of this systematic review with meta-analysis are twofold: (i) to summarize the primary physiological and physical fitness outcomes of lower-volume versus higher-volume training interventions in team sports players; and (ii) to compare the effects of lower-volume training with higher, considering the training modalities used.